Right Ventricular Myocardial Adaptation Assessed by Two-Dimensional Speckle Tracking Echocardiography in Canine Models of Chronic Pulmonary Hypertension - Yuchi, Yunosuke; Suzuki, Ryohei; Kanno, Haruka; Teshima, Takahiro; Matsumoto, Hirotaka; Koyama, Hidekazu (Frontiers in Veterinary Science, 2021)
Background: Pulmonary hypertension (PH) is a life-threatening disease in dogs characterized by an increase in pulmonary arterial pressure (PAP) and/or pulmonary vascular resistance. Right ventricle adapts to its pressure overload through various right ventricular (RV) compensative mechanisms: adaptive and maladaptive remodeling. The former is characterized by concentric hypertrophy and increased compensatory myocardial contractility, whereas the latter is distinguished by eccentric hypertrophy associated with impaired myocardial function. Objectives: To evaluate the RV adaptation associated with the increase of PAP using two-dimensional speckle tracking echocardiography. Animals: Seven experimentally induced PH models. Methods: Dogs were anesthetized and then a pulmonary artery catheter was placed via the right jugular vein. Canine models of PH were induced by the repeated injection of microspheres through the catheter and monitored pulmonary artery pressure. Dogs were performed echocardiography and hemodynamic measurements in a conscious state when baseline and systolic PAP (sPAP) rose to 30, 40, 50 mmHg, and chronic phase. The chronic phase was defined that the sPAP was maintained at 50 mmHg or more for 4 weeks without injection of microspheres. Results: Pulmonary artery to aortic diameter ratio, RV area, end-diastolic RV wall thickness, and RV myocardial performance index were significantly increased in the chronic phase compared with that in the baseline. Tricuspid annular plane systolic excursion was significantly decreased in the chronic phase compared with that in the baseline. The RV longitudinal strain was significantly decreased in the sPAP30 phase, increased in the sPAP40 and sPAP50 phases, and decreased in the chronic phase. Conclusions: Changes in two-dimensional speckle tracking echocardiography-derived RV longitudinal strain might reflect the intrinsic RV myocardial contractility during the PH progression, which could not be detected by conventional echocardiographic parameters.